A contemporary, empowered female figure? Towards a feminist reading of Frimpong-Manso's Life and Living It and The Perfect Picture. (1st March 2017) - Kwansah-Aidoo, Kwamena; Owusu, Joyce Osei
This article examines the contemporary Ghanaian female figure as portrayed in two video films by Shirley Frimpong-Manso: Life and Living It (2007) and The Perfect Picture (2009). Though the selected films individually foreground male and female subjectivities, they share similar recurring motifs in female characterization. Using the postfeminist and African feminist frameworks as conceptual lenses, we interrogate the precise ways in which the female characters are portrayed and note that the films emphasize women's freedom and choice – individualism and self-determination; challenge male dominance; encourage female sexual empowerment; and female friendship and bonding. We conclude that, in spite of a few instances where the two films appear to uphold normative notions of femininity, they overwhelmingly portray contemporary empowered female characters, framed within African feminist and postfeminist perspectives and cultures. Ultimately, the paper seeks to show the extent to which a feminist framework can initiate new thinking and affect wider social perceptions.